Direct-proportional length-based DNA computing implementation for elevator scheduling problem - Muhammad, Mohd. Saufee (2007)
Implementation and experimental procedures to solve an elevator scheduling problem using direct-proportional length-based DNA computing approach are presented in this paper. All possible travel path combinations of the elevators are encoded by oligonucleotides of length directly proportional to the elevators traveling time based on certain initial conditions such as elevators present and destination floors, and hall calls from a floor. Parallel overlap assembly is employed for initial pool generation and polymerase chain reaction for amplification. Gel electrophoresis is then performed to separate all the generated travel paths by its oligonucleotides lengths. The gel electrophoresis image is then captured to visualize the required optimal path. Experimental result shows that DNA computing approach can be well-suited for solving such real-world problem of this type of nature